2002
DOI: 10.1002/mde.1097
|View full text |Cite
|
Sign up to set email alerts
|

The existence of gender‐specific promotion standards in the U.S.

Abstract: This paper is motivated by the claim that promotion probabilities are lower for women than men. Using data from the 1984 and 1989 National Longitudinal Youth Surveys, this paper tests this claim and two related hypotheses concerning training and ability. It is found that females are less likely to be promoted than males, and females receive less training than males. The relationship between promotion and gender varies across occupations, however, suggesting that the alleged glass ceiling faced by women and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…A recent analysis of promotions using data from a cross section of establishments found lower rates of promotion for women than for men with similar observed characteristics and the same job-specific performance ratings (Blau and DeVaro 2007). Other studies have found similar results using different data (Cabral, Ferber, and Green, 1981;Olson and Becker, 1983;Cannings 1988;Spurr 1990;McCue 1996;Jones and Makepeace, 1996;Cobb-Clark 2001;Gjerde 2002;Ransom and Oaxaca 2005;Acosta 2006). In contrast, studies such as Stewart and Gudykunst (1982), Gerhart and Milkovich (1989), and Hersch and Viscusi (1996) have found the reverse result.…”
Section: Background and Previous Literaturesupporting
confidence: 59%
“…A recent analysis of promotions using data from a cross section of establishments found lower rates of promotion for women than for men with similar observed characteristics and the same job-specific performance ratings (Blau and DeVaro 2007). Other studies have found similar results using different data (Cabral, Ferber, and Green, 1981;Olson and Becker, 1983;Cannings 1988;Spurr 1990;McCue 1996;Jones and Makepeace, 1996;Cobb-Clark 2001;Gjerde 2002;Ransom and Oaxaca 2005;Acosta 2006). In contrast, studies such as Stewart and Gudykunst (1982), Gerhart and Milkovich (1989), and Hersch and Viscusi (1996) have found the reverse result.…”
Section: Background and Previous Literaturesupporting
confidence: 59%
“…The glass ceiling problem was originally observed within corporations (Mattis, 2004;and, for a review, Jackson and O'Callaghan, 2009). At a later stage, Olson and Becker (1983), Maume (1999), James (2000), and Gjerde (2002) identified the existence of a glass ceiling in different aspects of the labor market as well as of the social and political life. Arulampalam et al (2007) examine the glass ceiling effect in terms of wage employment by estimating the gender gap along the wage distribution in a selection of EU countries.…”
Section: B) Glass Ceiling In the Worldmentioning
confidence: 99%
“…Studies suggest that acting on this virtual social identity, in turn, can create a self-confirming stereotype (Brickson, 2000;Snyder, 1992). For example, despite studies showing that women sometimes meet higher standards for promotion (Gjerde, 2002), male managers continue to describe female managers as "less confident, less analytical, less emotionally stable, less consistent, and possessing poorer leadership abilities than male managers" (Oakley, 2000, p. 326). When women managers are subjected to differential treatment based on this virtual social identity, it can become a persistent, self-fulfilling stereotype.…”
Section: The Ongoing Importance Of Diversity Managementmentioning
confidence: 99%